Consciência corporal e educação física escolar: possibilidades de intervenção - Silva, Joadson Martins da (2011)
The investigation about the body consciousness in school Physical Education had as main objective reporting a possibility of intervention, linking it directly to the contents of Physical Education and considering it as a crosscutting theme in this research. In this scope, we worked specifically with two contents of Physical Education - knowledge about the body and fights. During the study, we are going to discuss about teaching strategies for the themes of body awareness. To develop this work, we used the following study questions: how is treated the body consciousness in Physical Education and how it has been addressed in educational interventions? What are the difficulties found to the themes of body awareness on different issues of school Physical Education? How body awareness thematized in contents in Physical Education is received by the students and what are the attitudes demonstrated by them during the development of these lessons? Based from questions of study, we used the following methodological tools: participant observation, interviews, photographic records, debates, films, dramatizations and dynamics, which they were performed to stimulate students' critical thinking about their body and the other children s one. The research with ethnographic characteristics was conducted in two schools: one elementary school I, in Natal and one elementary school II, held in the municipality of the João Câmara, in the state of Rio Grande do Norte. We developed a structure in order that the three dimensions of contents conceptual, procedural and attitudinal were experienced by students. The work is structured in five chapters. At first, we made an introduction to justify the motivations that led us to write about body awareness at school. In the second chapter, we discussed reflection about the body and its possibilities of understanding, reflecting on the body and how this awareness was being treated in physical education classes at school. In the third chapter, dealing with the body awareness and dialogue with the Physical Education, we had made a theoretical approach, from authors such as CLARO (1988), NÓBREGA (2000), ARAGÃO (2004), MELO (2006), LORENZETTO and MATTHIESEN (2008) in order to situate the body consciousness and its relationship with physical education. In the fourth chapter, we talked about body awareness thematized in physical education contents: knowledge about the body and fights. We introduced the teaching experience developed in the school and we discussed with authors such as OLIVIER (2000), DARIDO AND RANGEL (2008), among others, about how was the reflection about the body leaving of these experiences. The fifth chapter was intended to closing remarks, in which we concluded that the body awareness, treated in physical education in school by sociocultural and historical aspects, it will contribute in building a man, a body and a society. Although the body consciousness is crafted in a few moments of Physical Education, based on the practices of body awareness or alternatives; in our proposal, we pointed out another perspective to work with body awareness, bringing its elements to permeate and pass through the contents of Physical Education. At work we can see a suggestion for that these experiences are carried out by other Physical Education professionals, obviously adapting the activities according to age and educational level of students